The right to live in family: experience about the process of the tutelary research - Solórzano Mendoza de Pinto, Julia (2015)
This is a comment about the situation of the children without parental care, who live institutionalized in the Residential Care Centers, for long periods of time, because their processes of Tutelary Research are not solved. When the children and teenagers cannot return to a family environment, their rights are infringed, especially the right to live in a family environment that contributes to their protection, development and wellbeing. It is an analysis created out of a job  experience, about the situation lived by many children, even since they are born, to whom the system usually does not prioritize the resolution for their legal situation.